2021
DOI: 10.1111/jce.14947
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term clinical outcomes of cardiac sympathetic denervation in patients with refractory ventricular arrhythmias

Abstract: Background Cardiac sympathetic denervation (CSD) is a useful therapeutic option in patients with structural heart disease (SHD) and ventricular tachycardia (VT) who are otherwise refractory to standard antiarrhythmic drug (AAD) therapy or catheter ablation (CA). In this study, we sought to retrospectively analyze the long‐term outcomes of CSD in patients with refractory VT and/or VT storm with a majority of the patients being taken up for CSD ahead of CA. Methods We included consecutive patients with SHD who u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Symptoms of arrhythmias and ICD shocks were controlled for up to 20 years postoperatively in some patients. Long‐term clinical studies have shown significant declines in ICD shocks for VT up to 2 years post‐CSD 9 . Postoperatively, our patient did not experience any VT and had improved cardiac function.…”
Section: Discussionmentioning
confidence: 60%
“…Symptoms of arrhythmias and ICD shocks were controlled for up to 20 years postoperatively in some patients. Long‐term clinical studies have shown significant declines in ICD shocks for VT up to 2 years post‐CSD 9 . Postoperatively, our patient did not experience any VT and had improved cardiac function.…”
Section: Discussionmentioning
confidence: 60%
“…screened the abstracts and titles of the studies and subsequently reviewed the full-text articles for inclusion on the Covidence. 14 No language restriction was limited. A manual search for conceivably relevant studies using references of the included articles was also performed.…”
Section: Methodsmentioning
confidence: 99%
“…The latest retrospective single institutional studies indicate that if other treatment modalities such as pharmacological medication, ICD and catheter ablation fail to achieve optimal results, bilateral thoracoscopic cardiac denervation is a safe and feasible method with promising results. Most studies show an effectiveness of 70 -80 % in the fi rst month through one-year follow-up period after the procedure (18,19).…”
Section: Conclusion and Discussionmentioning
confidence: 99%